Effect of High Hydrostatic Pressure and Thermal Processing on the Shelf Life and Quality Attributes of Apple-Kiwi-Carrot Puree Blend - Xuezhi Tian; Yunshu Yang; Wenjing Zhang; Yongtao Wang (Journal of Food Quality)
The effects of high hydrostatic pressure (HHP) (400 MPa/2 min and 500 MPa/2 min) and thermal processing (TP) (90°C/2 min) on the microorganisms, nutrition, color, endogenous enzyme activities, antioxidant capacity, and rheological properties of blended apple-kiwi-carrot puree were comprehensively evaluated after processing and during storage at 4°C. Results showed the microbiological shelf life of the HHP or TP products was at least 24 days. TP inactivated polyphenol oxidase activity more effectively, retaining more polyphenols in samples during storage, whereas HHP treatments were more beneficial for the preservation of ascorbic acid, total carotenoids, β-carotene, and antioxidant capacity. During storage, there was no significant difference in PME activity among all treated samples, but particle size distribution and viscoelasticity tests demonstrated that the 400 MPa treated samples were more stable in their textures. Moreover, the principal component analysis (PCA) intuitively revealed that the overall sensory and nutritional attributes of the HHP-treated samples were closer to the fresh product. These results demonstrated that HHP could be a better choice than TP for use in the production of high-quality puree blends.